"METHODS OF ENGAGING YOUNG LEARNERS IN LEARNING THE ENGLISH LANGUAGE" - Mirzakarimova Aziza (Journal of new century innovations, 2024)
This article highlights the significant importance of teaching foreign languages in the Republic of Uzbekistan and the necessary innovative technologies for learning them. Since gaining independence, interest in learning foreign languages has increased in our country, and various opportunities have been created for young people. As our first president, Islam Karimov, stated, "Teaching foreign languages is of great importance in our country today. This is not optional. Our nation, which is striving to take its rightful place in the world community and is building its great future in cooperation with our foreign partners, needs to appreciate the importance of mastering foreign languages." As a logical continuation of these ideas, the Presidential Decree on further improving the system of teaching foreign languages, adopted on December 10, 2012, expanded the opportunities for learning foreign languages. In our republic, the teaching of foreign languages, the evaluation of the knowledge and skills of foreign language teachers according to the Common European Framework of Reference for Languages (CEFR), new methods and requirements were developed.